The status of Rangifer tarandus caribou in Yukon, Canada - Farnell, R.; Florkiewicz, R.; Kuzyk, G.; Egli, K. (Rangifer, 1998)
This paper summarizes the population trends as well as research and management programs for woodland caribou {Rangifer tarandus caribou) in Yukon. Most herds are stable although not all are counted regularly and systematic monitoring of herds remains an essential need. Over the past decade the Southern Lakes, Aishihik, and Finlayson herds have been well studied and provide valuable models for guiding Yukon management programs. Over harvest and the spread of agriculture, forestry and mining are ongoing human activities are of concern to caribou managers.